2021
DOI: 10.1038/s41467-021-21714-2
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity tunable ceria nanoparticles prevent chemotherapy-induced acute kidney injury without interference with chemotherapeutics

Abstract: Acute kidney injury (AKI) is a prevalent and lethal adverse event that severely affects cancer patients receiving chemotherapy. It is correlated with the collateral damage to renal cells caused by reactive oxygen species (ROS). Currently, ROS management is a practical strategy that can reduce the risk of chemotherapy-related AKI, but at the cost of chemotherapeutic efficacy. Herein, we report catalytic activity tunable ceria nanoparticles (CNPs) that can prevent chemotherapy-induced AKI without interference wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 70 publications
2
144
0
Order By: Relevance
“…In recent years, cerium oxide nanoparticles (CeO 2 NPs, nanoceria) have been received momentous interest owing to their inimitable physiochemical properties, biocompatibility, and bioactivities 14 , 15 . They were broadly exploited in various fields such as therapeutics agents in acute kidney injury 16 , catalysis, drug delivery careers, and environmental pollution scavenger 17 . It is found that effective oxidative stress, free-radical scavengers’ role, and enzyme-mimetic catalytic performance of nanoceria mostly due to variation between the Ce 4+ and Ce 3+ cations proportion which on account of oxygen deficiencies in lattice arrangement of their crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cerium oxide nanoparticles (CeO 2 NPs, nanoceria) have been received momentous interest owing to their inimitable physiochemical properties, biocompatibility, and bioactivities 14 , 15 . They were broadly exploited in various fields such as therapeutics agents in acute kidney injury 16 , catalysis, drug delivery careers, and environmental pollution scavenger 17 . It is found that effective oxidative stress, free-radical scavengers’ role, and enzyme-mimetic catalytic performance of nanoceria mostly due to variation between the Ce 4+ and Ce 3+ cations proportion which on account of oxygen deficiencies in lattice arrangement of their crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Ceria NPs can catalyze the dismutation of ·O 2 − into H 2 O 2 at both neutral and acidic pH values, as well as decomposing H 2 O 2 under neutral, but not acidic, pH. Therefore, ceria NPs exerted a general cytoprotection on cells that were challenged by oxidizing chemotherapeutics at a neutral pH, without compromising their anti-tumor activity at an acidic pH, which is a common feature of tumor microenvironments ( Figure 11 ) [ 119 ]. Ceria NPs demonstrated a promising performance to partially revert the cellular mechanisms involved in tumor progression.…”
Section: (Bio)applicationsmentioning
confidence: 99%
“…( a ) In the acidic tumor microenvironment, ceria NPs ROS scavenging ability is switched off and does not interfere with oxidizing chemotherapeutics; ( b ) in the neutral pH of the kidneys, ceria NPs scavenge ROS and exert cytoprotection. Reproduced from [ 119 ], under a Creative Commons license .…”
Section: Figurementioning
confidence: 99%
“…with agents that can block drug transporters, such as cimetidine). Downstream effects of mitochondrial toxicity, including reactive oxide species (ROS) generation, may also be targeted to limit cellular damage [35].…”
Section: Cellular Mechanisms Of Drug Toxicity In the Proximal Tubulementioning
confidence: 99%